Toward a Whole-of-Europe Approach: Organizing the European Union’s and Member States’ Comprehensive Crisis Management - Post, Svenja (Springer, 2015)
With her research, Svenja Post offers an in-depth analysis of the implementation of the Comprehensive Approach in international crisis management both on EU and on member state national level. The author demonstrates in detail which steps have been taken on conceptual and on structural level by the EU and its member states Great Britain, Germany and Sweden to organize and realize crisis management coherence. In addition to identifying challenges involved actors are confronted with, Svenja Post also points out a set of recommendations for future efforts to close the gap between aspiration and reality of comprehensive European crisis management.